Practical body MRI : protocols, applications, and image interpretation - Grand, David J.; Mayo-Smith, William W.; Woodfield, Courtney A. (Cambridge medicine, 2012)
"Practical Body MRI: Protocols, Applications and Image Interpretation demystifies MRI examinations of the abdomen and pelvis, giving the essential knowledge required by radiologists in order to develop and select appropriate protocols, assess scan quality and interpret imaging studies. Each chapter describes why each sequence is performed, what to look for, and how the important findings from each sequence lead to a unique diagnosis. Numerous protocols are included, from the more common, such as liver and renal MRI, to more tailored examinations such as rectal and placental MRI. All protocols are richly illustrated with images of body MR pathology. A separate chapter discusses MRA/MRV and an introductory chapter gives a brief, practical introduction to MRI physics and receiver coils. The authors' expertise and practical, concise explanations of both protocols and image interpretation makes this an essential resource for residents, fellows and experienced radiologists using bodyMRI for the first time" -- Provided by publisher.